2015
DOI: 10.1016/j.schres.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructural abnormalities of the cingulum bundle in youths with 22q11.2 deletion syndrome: Associations with medication, neuropsychological function, and prodromal symptoms of psychosis

Abstract: Background The 22q11.2 Deletion Syndrome (22q11.2DS) is regarded as an etiologically homogenous model for understanding neuroanatomic disruptions associated with a high risk for schizophrenia. This study utilized diffusion tensor imaging (DTI) to analyze white matter microstructure in individuals with 22q11.2DS. We focused on the cingulum bundle (CB), previously shown to be disrupted in patients with schizophrenia and associated with symptoms of psychosis. Methods White matter microstructure was assessed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 93 publications
12
34
0
Order By: Relevance
“…The effect of antipsychotic and mood stabilizer medication was reported previously in cingulum bundle in this data set and had a reparative outcome: It was observed that the subgroup of youth with 22q11DS that was given a low dose of antipsychotic or mood stabilizer medication currently or in the past, had the same FA and AD values in the cingulum bundle as the controls, while the non-medicated subjects with 22q11DS had significantly lower values in FA and AD (Kates et al 2015). While in our current analysis, the subjects with the high score on BPRS-psychosis symptoms were more medicated than those with a low score, the AD values were lowest in the subjects with high score on BPRS-psychosis symptoms.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The effect of antipsychotic and mood stabilizer medication was reported previously in cingulum bundle in this data set and had a reparative outcome: It was observed that the subgroup of youth with 22q11DS that was given a low dose of antipsychotic or mood stabilizer medication currently or in the past, had the same FA and AD values in the cingulum bundle as the controls, while the non-medicated subjects with 22q11DS had significantly lower values in FA and AD (Kates et al 2015). While in our current analysis, the subjects with the high score on BPRS-psychosis symptoms were more medicated than those with a low score, the AD values were lowest in the subjects with high score on BPRS-psychosis symptoms.…”
Section: Discussionsupporting
confidence: 70%
“…Further, our previous study by Perlstein et al (2014) and by Kates et al (2015), showed evidence of reduced FA in anterior limb of the internal capsule and the uncinate fasciculus, as well as reduced FA in the cingulum bundle, respectively. In these studies the tracts were preselected and tractography measures were used to determine whether or not these tracts were affected.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…DTI facilitates the in vivo study of brain white matter (WM) microstructure (Mori et al, 2008), and typical DTI measures include fractional anisotropy (FA), mean (MD), axial (AD) and radial diffusivity (RD). Alterations in these metrics are reported in 22q11DS (Barnea-Goraly et al, 2003; da Silva Alves et al, 2011; Deng et al, 2015; Kates et al, 2015; Kikinis et al, 2012; Martin et al, 2014; Ottet et al, 2013; Padula et al, 2015; Radoeva et al, 2012; Scariati et al, 2016; Sundram et al, 2010; Villalon-Reina et al, 2013), and some of the patterns observed are similar to deficits in SZ (Kyriakopoulos et al, 2008; Roalf et al, 2015; Thomason and Thompson, 2011), adolescents with psychosis (Davenport et al, 2010; White et al, 2007) and youth at risk for developing psychosis (Epstein et al, 2013; Lee et al, 2013). In contrast to structural gray matter findings, DTI results in 22q11DS are more inconsistent.…”
Section: 0 Introductionmentioning
confidence: 85%